The evolution of Islamic rhetoric in Malaysian political discourse - Mohamad Jamil, Siti Nurnadilla; Mohamad Shukri, Syaza Farhana (Springer Nature, 2026)
This chapter delves into the evolution of political oratory in Malaysia, focusing on the transformation of Islamic issues from the 1980s onwards. Traditionally, Malaysian political discourse was shaped by bureaucratic perspectives under United Malay Nasional Organization’s (UMNO) regime, using Islamic issues to maintain its political dominance and socio-political stability. However, this landscape underwent significant changes in the face of Islamic revivalism and the subsequent global maelstrom of Islamophobia that popularized a more appealing rhetoric of “moderate Islam” since the early 2000s. In 2022, the Anwar Ibrahim administration revisited Islamic rhetoric under the Malaysia Madani (“Civilized Malaysia”) framework, showcasing the perpetual link of Islamic rhetoric within Malaysian politics. This chapter analyzes significant speeches by selected prime ministers—Mahathir Mohamad, Abdullah Badawi, Najib Razak, and Anwar Ibrahim—immediately after becoming prime minister or winning an election to illustrate their roles in this rhetorical shift. The analysis draws on critical discourse analysis, focusing on homiletics, as persuasive religious rhetoric to convey moral or spiritual teachings. In politics, this translates into aligning Islamic rhetoric with audiences’ values to strengthen the speaker’s authority and political legitimacy amid growing religio-political conservatism.